Enhancing nickel stress tolerance in Micro-Tom tomatoes through biopriming with Paraburkholderia phytofirmans PsJN: insights into growth and physiological responses - Hasanović, Mujo; Durmić-Pašić, Adaleta; Karalija, Erna (Frontiers in Microbiology, 2025)
IntroductionThe strategic utilization of plant growth-promoting (PGP) rhizospheric bacteria is a sustainable approach to mitigating the negative effects of anthropogenic activities and excessive nickel (Ni) accumulation in plants. Given that the specific effects of symbiotic interactions depend on the direct relationship between the plant species, bacterial strain, and heavy metals (HMs), this study aimed to investigate the effects of Paraburkholderia phytofirmans PsJN seed priming on Ni tolerance in adult Micro-Tom tomato plants (Solanum lycopersicum L.).MethodsSterilized Micro-Tom seeds were bioprimed with P. phytofirmans PsJN for 24 hours and then sown into the soil. Non-primed, imbibed seeds were used as a control. After 10 days, the seedlings were transferred to a Hoagland nutrient solution. Chronic (10 μM Ni) and acute (50 μM Ni) stress conditions were induced by supplementing the Hoagland solution with Ni salt. The experiment lasted approximately 75 days, covering the complete life cycle of the plants. Various physiological and biochemical parameters were analyzed.ResultsSignificant differences (p < 0.05) were observed between non-primed and bioprimed tomato plants in terms of fruit yield. Bioprimed tomatoes exhibited higher resilience to Ni stress, particularly under acute stress conditions. Non-primed tomatoes treated with 50 μM Ni showed statistically lower concentrations of chlorophyll a and total chlorophylls compared to bioprimed tomatoes. Moreover, proline content was generally lower and more stable in bioprimed plants, indicating reduced oxidative stress.The activity of antioxidant enzymes exhibited distinct patterns between nonprimed and bioprimed tomatoes.ConclusionThe findings suggest that biopriming with P. phytofirmans PsJN enhances Micro-Tom tomato resilience and growth under Ni stress. This technique appears to mitigate Ni-induced stress effects, particularly at higher Ni concentrations, making it a promising strategy for improving tomato performance in Ni-contaminated environments. Future studies should explore the underlying molecular mechanisms and field applications of this biopriming approach.